Occupational gender segregation in post-apartheid South Africa - Carlos Gradín (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
In this paper, I show that occupations in South Africa are segregated and stratified not only by race, but also by gender. While some women (mostly black and Coloured) overwhelmingly fill low-paying jobs, others (mostly white and Indian/Asian but also Coloured) tend to fill higher-paying professional positions. I find some evidence of a long-term reduction in gender segregation and stratification, with women and men entering occupations previously dominated by the other gender, although this trend is sensitive to several data considerations. Most recent evidence, however, points at stagnation in this process. Distinct worker characteristics by gender, such as education, location, or age, cannot explain existing segregation or women's overrepresentation in low-paying jobs, compared with men. They do, however, partially explain their overrepresentation in higher-paying positions.
Keywords: J16; J42; J71; J82; O15; O55; 330; gender; occupational segregation; stratification; low pay; post-apartheid; South Africa